Uncertainty in the Early Phase of a Municipal Building Refurbishment Project—A Case Study in Finland - Ulrika Uotila; Arto Saari; Juha-Matti Junnonen (Buildings, 2020)
Municipal building refurbishment projects are carried out under conditions of high uncertainty and complexity, which often result in unsatisfying outcomes. In this research, a case study approach is used to provide a holistic presentation of the sources of uncertainties in the early phase of a municipal school refurbishment project in Finland. The study also explores how these sources are treated in the case project. It is considered that the uncertainty in the case study originated from three key sources: from the project due to the characteristics of existing buildings; from the organization due to the separately operating municipal units; from the municipal environment due to the municipal policy, and decision-making process. This study shows that more emphasis should be laid on the sources of uncertainty in the early phases of a municipal building refurbishment project for reaching proper decisions. In addition, the study presents suggestions for improving the municipal process.